La viande rouge : un critère de virilité dans la Rome antique ? IIe siècle-IIe siècle ap. J.-C.) - Christophe Badel (Genre & Histoire)
Unlike the contemporary period, red meat had no special relationship with manliness in ancient Rome. Centred on self-control, and not on strength, Roman manliness had nothing to do with a food, otherwise deprecated, which contributed nothing in this field. As the embodiment of civilization, the vir had no attraction for a matter gorged with blood that placed it on the side of nature and rawness. In terms of taste, Roman males preferred white meat, which was the delight of aristocratic banquets. According to doctors, red meat was more dangerous for women than for men, but they also advised men not to consume it. On the subject, there was no symmetrical opposition between the two genres, but rather a gradient on a common continuum of negative nature.